Performance measurement system change: a consulting company perspective. (1st January 2012) - Guerrini, Andrea
This article explores how consulting companies develop performance measurement system change (PMSC) through an analysis of the processes, tools and techniques they adopt and the internal actors involved. Moreover, it aims to demonstrate the existence of a situational approach in changing a PMS related to the nature of services provided by each consulting company. In a multiple case study, the author selected 18 consulting companies that offer PMSC services and collected data through 36 partially structured interviews (two managers from each company) and a brainstorming session with three consultants from different firms. The data were analysed using cross-case and within case analysis and descriptive statistics.